Processo de implantação de uma usina solar fotovoltaica localizada no município de Porto Nacional – Tocantins - Luz Junior, Valter Luiz Ribeiro Da (Universidade Federal do Tocantins, 2022)
Renewable energy sources, as is the case with solar energy, are gaining space in the market every day and this is due to the great concern of the population in relation to environmental preservation, in the increasing value of energy tariffs, the search for self - sufficiency energy, growing demand in particular such as the electrification of transport and global warming, new business models, subsidies such as feed-in tariff and reduction in the cost of acquiring and maintaining technology. In this way, the present project has the general objective to describe the process of implementing solar energy in a solar plant located in the municipality of Porto Nacional-TO. A series of steps were followed so that the process progressed in a fundamental way to reach the final objective. The specific objectives are: to evaluate the benefits of implementing an electric power generation system using photovoltaic modules; analyze the economic and financial feasibility of photovoltaic solar energy as an alternative for cost reduction and energy diversification; analyze the implementation of photovoltaic modules and their impacts on nature. The methodology used was the monitoring of the photovoltaic plant, followed by a sequence of steps, outlined by a cross-sectional study with a quantitative approach. Each step was followed gradually and sequentially for the perfect performance of each step. The research was carried out in the city of Porto Nacional, state of Tocantins, in a solar plant located in this municipality. The research period comprised the months of August to October 2021.